2015
DOI: 10.2174/157340561103150629120838
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Efficiency of Radiation Protection Training in Raising Awareness of Medical Staff Working in Catheterisation Laboratory

Abstract: The purpose of this study is to conduct a systematic review of the efficiency of radiation protection (RP) training in minimising the radiation dose to both medical staff and patients.The literature search for the relevant articles was performed using five different databases which included Scopus, ScienceDirect, PubMed, Medline and ProQuest. The search covered English language publications in the period between 2000 and 2014. The search was also limited to peer-reviewed articles on human subjects and reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This result was contrary to the results obtained from the study of (26)(27)(28). based on our study and con rmation of studies Briggs-kamara et al and Ria et al, it was found that patients' awareness was de cient (18,19,26,29,30), It should be noted that in our study, most radiation students and staff thought they were well aware and did not need to undergo training. However, in studies Masoumi et al and Rostamzadeh et al, it was found that training reduces radiation risks and increases radiation awareness (27,31).…”
Section: Discussionsupporting
confidence: 84%
“…This result was contrary to the results obtained from the study of (26)(27)(28). based on our study and con rmation of studies Briggs-kamara et al and Ria et al, it was found that patients' awareness was de cient (18,19,26,29,30), It should be noted that in our study, most radiation students and staff thought they were well aware and did not need to undergo training. However, in studies Masoumi et al and Rostamzadeh et al, it was found that training reduces radiation risks and increases radiation awareness (27,31).…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have shown that cardiologists formally trained in RP are more aware of radiation safety than those who are untrained (17,18) . A recent systematic review showed that RP training can efficiently raise the awareness of medical staff working in a catheterization laboratory and reduce their exposure to radiation doses (19) . The International Commission on Radiological Protection (ICRP) indicates that interventional procedures are mainly operator dependent with slight variances in techniques and roles existing among centers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that radiation safety education improved compliance with radiation safety procedures in medical staff who participated in interventional procedures, reducing their exposure to radiation (Alahmari & Sun, ; Sheyn et al., ), and that nurses’ knowledge of and attitudes towards radiation safety can be enhanced through safety education (Dauer, Kelvin, Horan, & Germain, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that radiation safety education improved compliance with radiation safety procedures in medical staff who participated in interventional procedures, reducing their exposure to radiation (Alahmari & Sun, 2015;Sheyn et al, 2008), and that nurses' knowledge of and attitudes towards radiation safety can be enhanced through safety education (Dauer, Kelvin, Horan, & Germain, 2006). Therefore, the ICRP and other concerned academic institutions recommend safety education for medical workers to control radiation safely (Chen, 2014;ICRP, 2009;Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%